Retention failures in cement- and screw-retained fixed restorations on dental implants in partially edentulous arches: A systematic review with meta-analysis - Jatin K Jain; Rajesh Sethuraman; Sameer Chauhan; Piyush Javiya; Shreya Srivastava; Rutvik Patel; Bhagyashri Bhalani (Wolters Kluwer Medknow Publications, 2018)
Purpose: This systematic review aimed to evaluate retention failures in cement- and screw-retained fixed restorations on dental implants in partially edentulous arches. Methods: The relevant articles were retrieved from MEDLINE (PubMed), Cochrane Library, and EBSCO electronic databases for articles published from January 1995 to January 2016 and were restricted to randomized controlled trials and retrospective and prospective studies on human subjects that were reported in English. A further hand search was conducted on individual journals and reference list of the articles found. Reviewed studies which reported retention failures in fixed implant-supported prostheses using screw and cement retention mechanism. Information on the type and nature of restoration, as well as different luting cement, were also collected. Results: Thirty-three articles were finalized, 20 short-term clinical studies (up to 5 years) and 13 long-term studies (≥5 years). Out of 33 studies, 16 studies were included in meta-analysis, 8 in short-term and 8 in long-term studies. The results of the meta-analysis for short-term studies showed statistically significant difference between cement-retained and screw-retained prosthesis, with the forest plot favoring cement-retained prostheses (risk ratio [RR]: 0.26; confidence interval [CI]: 0.09-0.74; P < 0.0001; I2 = 79%). In long-term studies, the forest plot revealed statistically significant difference between both retention systems favoring cement-retained prostheses (RR: 0.31; CI: 0.13-0.76; P = 0.03; I2 = 56%). Conclusion: Analysis of the short- and long-term studies shows lesser retention failures with cement-retained prostheses when compared to screw-retained prostheses. Further, multicentric, high-quality randomized controlled studies with long-term observations and modified cementation protocols can yield higher grades of recommendation to avoid retention failures.